A population representation of the confidence in a decision in the parietal cortex - Ariel Zylberberg; Michael N. Shadlen (Cell Reports)
Summary: Many decisions arise from a race between competing evidence accumulation processes that terminate upon reaching a threshold. We ask whether neurons supporting this accumulation also encode confidence—whether a choice is correct or incorrect. Monkeys performed a reaction-time random dot motion task while populations of neurons were recorded from the lateral intraparietal (LIP) area. Shortly before the choice report, LIP neurons with response fields overlapping the contralateral choice target (Tin neurons) convey information about choice accuracy. We show that this information would give rise to the behavioral signatures of confidence observed in humans. These findings are surprising because the activity of Tin neurons just before the report is, on average, independent of reaction time and motion strength—strong predictors of accuracy. This tension is resolved by considering the heterogeneity of neuronal responses across the population of Tin neurons. We conclude that neurons representing evidence accumulation may inform a decision-maker’s confidence.